Peranan Guru Bimbingan Konseling Terhadap Layanan Pendidikan Inklusi - Amiroh ami; Ika Ika; Siti Soliah (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
The purpose of this study was to find out about the role of guidance and counseling teachers in inclusive education services at MAS Nurul Falah Ciater. This type of research is descriptive qualitative with narrative analysis techniques. The main informants consisted of 1 counseling teacher and 3 inclusive students. Data collection techniques in this study used interviews, observation, and documentation. Data analysis from the results of this study was carried out by descriptive analysis. The results of the study show that 1) the role of the guidance and counseling teacher in inclusive education services at MAS Nurul Falah Ciater is very important and the problems or constraints of inclusive students can be handled very well by the guidance and counseling teacher; 2) The obstacles faced by guidance and counseling teachers are the lack of facilities and infrastructure that can support the implementation of the inclusion program effectively; 3) Solutions that need to be implemented to maximize inclusion programs in schools include intensifying school evaluation programs, participating in training or BIMTEK related to inclusion services, and supervisory relationships or networks to monitor teacher work programs so that they are better and more planned. Keywords: Role; Counselling Guidance Teacher; and Inclusive Education Services